Turmeric supplementation improves markers of recovery in elite male footballers: a pilot study - Clayton, David J.; Burbeary, Ross; Hennis, Philip J.; James, Ruth M.; Saward, Christopher; Colledge, Amy; Scott, Reece; Gilpin, Steve; McMahon, Ryan; Varley, Ian (Frontiers in Nutrition, 2023)
Football match-play causes muscle damage and provokes an inflammatory response. Rapid recovery is paramount to optimising subsequent performance and reducing injury risk. Turmeric contains high concentrations of curcumin, a polyphenol that has been shown to reduce muscle damage and soreness post-exercise in recreational exercisers. However, it is unknown whether a curcumin-containing supplement can support elite footballers recovery between matches. This applied study explored whether a turmeric supplement could improve performance, subjective and physiological markers of recovery, in elite male footballers. Twenty-two elite male footballers divided into a turmeric group, who consumed 60mL of a turmeric drink twice per day, or a control group who did not. After 96 h of rest, baseline measurements of subjective leg and whole-body soreness, isometric mid-thigh pull (IMTP) and counter movement jump (CMJ), and plasma creatine kinase ([CK]) and C-reactive protein ([CRP]). Following eight competitive matches, subjective leg and whole-body soreness and plasma concentrations of inflammation markers ([CK] and [CRP]) were assessed immediately (0 h), 40 and 64 h post-match. Performance markers (IMTP and CMJ) were also assessed at 40 and 64h post-match. Percentage change from baseline showed a main effect of group (P=0.035, P=0.005) and time (P=0.002, P=0.002) for both leg and whole-body soreness, respectively. There was a group by time interaction effect (P=0.049) for [CRP]. There were no effects of turmeric on [CK], CMJ or IMTP. This applied study is the first in elite footballers to show that a curcumin-containing supplementation may attenuate a biomarker of inflammation [CRP] and soreness post-match play.